A model for the evolution of the Earth's mantle structure since the Early Paleozoic - Zhang, N.; Zhong, S.; Leng, W.; Li, Zheng-Xiang (American Geophysical Union, 2010)
Seismic tomography studies indicate that the Earth's mantle structure is characterized by African and Pacific seismically slow velocity anomalies (i.e., superplumes) and circum-Pacific seismically fast anomalies (i.e., a globally spherical harmonic degree 2 structure). However, the cause for and time evolution of the African and Pacific superplumes and the degree 2 mantle structure remain poorly understood with two competing proposals. First, the African and Pacific superplumes have remained largely unchanged for at least the last 300 Myr and possibly much longer. Second, the African superplume is formed sometime after the formation of Pangea (i.e., at 330 Ma) and the mantle in the African hemisphere is predominated by cold downwelling structures before and during the assembly of Pangea, while the Pacific superplume has been stable for the Pangea supercontinent cycle (i.e., globally a degree 1 structure before the Pangea formation). Here, we construct a proxy model of plate motions for the African hemisphere for the last 450 Myr since the Early Paleozoic using the paleogeographic reconstruction of continents constrained by paleomagnetic and geological observations.Coupled with assumed oceanic plate motions for the Pacific hemisphere, this proxy model for the plate motion history is used as time-dependent surface boundary condition in three-dimensional spherical models of thermochemical mantle convection to study the evolution of mantle structure, particularly the African mantle structure, since the Early Paleozoic. Our model calculations reproduce well the present-day mantle structure including the African and Pacific superplumes and generally support the second proposal with a dynamic cause for the superplume structure. Our results suggest that while the mantle in the African hemisphere before the assembly of Pangea is predominated by the cold downwelling structure resulting from plate convergence between Gondwana and Laurussia, it is unlikely that the bulk of the African superplume structure can be formed before ∼230 Ma (i.e., ∼100 Myr after the assembly of Pangea). Particularly, the last 120 Myr plate motion plays an important role in generating the African superplume. Our models have implications for understanding the global-scale magmatism, tectonics, mantle dynamics, and thermal evolution history for the Earth since the Early Paleozoic.